FUZZY MODEL FOR ASSESSING THE QUALITY OF MONITORING OF NATURAL AND MAN-MADE THREATS - Yesmagambetova М.; Koshekov К.; Alibekkyzy К.; Belginova С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The purpose of the work is to improve the quality of the management process of the territorial service for monitoring and preventing emergencies. It is proposed to achieve the goal by improving the information and analytical support of the territorial system for monitoring and forecasting emergency situations of natural and man-made origin. The solution of the problems of this problem is carried out on the example of control and prevention of flood situations on a regional scale. East Kazakhstan region was chosen as the region. In the proposed study, two scientific and practical tasks are solved: the development of a formal method for quantitative assessment of the quality of management of a complex multi-criteria organizational and technical system in conditions of parametric fuzziness; formalization of the process of quantitative assessment of decision-making risks in the environment of statistical uncertainty of control agents. To solve the first problem, a structural model for a differentiated assessment of the quality of management based on a fuzzy approach and a model for an integrated convolution of differentiated indicators have been developed. To solve the second problem of assessing and predicting the risks of control and decision-making, under conditions of statistical uncertainty, a probabilistic model has been developed. The verification of theoretical assumptions is implemented by computer simulation using a software application developed for this purpose.